Chlamydia pneumoniae Infection Induces Vascular Smooth Muscle Cell Migration and Atherosclerosis Through Mitochondrial Reactive Oxygen Species-Mediated JunB-Fra-1 Activation - Zhao, Xi; Miao, Guolin; Zhang, Lijun; Zhang, Yuke; Zhao, Huanhuan; Xu, Zhelong; Wang, Beibei; Zhang, Lijun (Frontiers in Cell and Developmental Biology, 2022)
Infection is closely related to atherosclerosis, which is a major pathological basis for cardiovascular diseases. Vascular smooth muscle cell (VSMC) migration is an important trigger in development of atherosclerosis that is associated with Chlamydia pneumoniae (C. pneumoniae) infection. However, the mechanism of VSMC migration remains unclear, and whether antioxidant could be a therapeutic target for C. pneumoniae infection-induced atherosclerosis also remains unknown. The results showed that C. pneumoniae infection mainly impaired mitochondrial function and increased the level of mitochondrial reactive oxygen species (mtROS). The expressions of protein JunB, Fra-1 and Matrix metalloproteinase 2 (MMP) evidently increased after C. pneumoniae infection, and the interaction between JunB and Fra-1 was also enhanced. After scavenging mtROS by antioxidant Mito-TEMPO, the increasing expressions of JunB, Fra-1, MMP2 and the capacity of VSMC migration induced by C. pneumoniae infection were all inhibited. In comparison with infected ApoE-/- mice, the level of ROS in atherosclerotic lesion in ApoE-/-TLR2-/- mice with C. pneumoniae infection decreased. Knocking out TLR2 suppressed the expressions of JunB, Fra-1 and MMP2 in VSMCs and the formation of atherosclerotic lesion after C. pneumoniae infection. Furthermore, after using small interfering RNA to inhibit the expression of TLR2, the level of mtROS and the expressions of JunB, Fra-1 and MMP2 apparently decreased. Taken together, C. pneumoniae infection may promote VSMC migration and atherosclerosis development by increasing the level of mtROS through TLR2 to activate the JunB-Fra-1/MMP2 signaling pathway. The data provide the first evidence that antioxidant could reduce C. pneumoniae infection-induced VSMC migration and atherosclerosis.